Analysis of the Toilet Training Program for Visually Impaired Students at SKH Negeri 01 Pandegelang (International Journal of Education and Literature, 2025)
The toilet training program for blind students at the State Special School (SKhN) 01 Pandegelang is an important aspect in the development of basic life skills. Blind students need to be trained systematically and continuously. This study used a qualitative approach. Data collection techniques were carried out through observation, in-depth interviews with teachers, students and parents, and documentation of the learning program implemented at the school. The results of the study indicate that the toilet training program at SKh Negeri 01 Pandegelang has been designed based on the individual needs of students, by implementing routine-based learning strategies, positive reinforcement, and the use of learning media that can be accessed tactilely and auditorily. Obstacles faced in the implementation of the program include limited special educators, lack of supporting facilities. Nevertheless, this program has a positive impact on increasing the independence of blind students in terms of personal hygiene, discipline, and self-confidence. The conclusion of this study shows that the success of the toilet training program is greatly influenced by teacher involvement, collaboration with parents, and adaptation of learning methods that are appropriate to the characteristics and needs of blind students. Researchers recommend strengthening teacher training, providing disability-friendly facilities, and regular program evaluations to improve optimal results